EXPECTED INCOME–A REPORTING CHALLENGE. - Schattke, Rudy (The Accounting Review, 1962)
The article suggests that disclosure in published reports is not complete unless expected income data are reported. Since a means for reporting such data is available, it is suggested that accountants thoroughly investigate the difficulties and drawbacks in such reporting, and, if they can satisfy themselves, press vigorously for it. Expectations and expected income are prime factors in influencing production, employment and profit results, and thus may be characterized as basic economic factors. Since it is customary to budget financial position as well as operations, it would probably be possible to report an anticipated balance sheet as well as an income statement. Auditors might come to regard a report of expected income and a contrast of results with previous expectations as a significant addition to the means available for disclosure of financial information, once they recover from their initial reaction. This initial reaction, however, based on a reluctance to deal with anything so hypothetical, would lead most members of the profession to banish all consideration of such a report from their minds.